EXPLORING OF JUNIOR HIGH SCHOOL STUDENTS' STATISTICAL LITERACY ABILITIES IN SOLVING STATISTICAL PROBLEM - Marchy, Febrinna; Martadiputra, Bambang Avip Priatna; Nurlaelah, Elah; Naser, Abdurrahman Do. Muhamad (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Statistical literacy is crucial in the digital era, where data influences decision-making. However, Indonesian students still struggle with interpreting and critically evaluating statistical information.This research aims to explores the statistical literacy abilities of ninth-grade students in a public junior high school in Bandung. Employing a phenomenological methodology, the study aims to provide a comprehensive description of students' proficiency in statistical literacy, identifying challenges they encounter. Data was collected through tests, interviews, and observations, with four students selected for in-depth interviews based on distinct test responses. The study focuses on five indicators: understanding components of statistics, interpreting messages, communicating messages, making decisions, and critically evaluating statistical information. Results indicate a varying level of statistical literacy among students, with 72.5% understanding statistical components but decreasing proficiency in interpreting (65.2%), communicating (41.7%), making decisions (38.9%), and critically evaluating information (38.0%). Detailed analysis of student responses illustrates conceptual errors and challenges in applying statistical concepts to practical decision-making scenarios. The study emphasizes the importance of developing analytical skills and applying statistical concepts in everyday life to enhance students' ability to critically evaluate information and make informed decisions.Literasi statistik sangat penting di era digital, di mana data memengaruhi pengambilan keputusan. Namun, siswa di Indonesia masih kesulitan dalam menafsirkan dan mengevaluasi informasi statistik secara kritis. Penelitian ini bertujuan untuk mengeksplorasi kemampuan literasi statistik siswa kelas IX di salah satu SMP Negeri di Bandung. Dengan menggunakan metodologi fenomenologi, penelitian ini bertujuan untuk memberikan gambaran komprehensif tentang kemampuan siswa dalam literasi statistik, dan mengidentifikasi tantangan yang mereka hadapi. Data dikumpulkan melalui tes, wawancara, dan observasi, dengan empat siswa dipilih untuk wawancara mendalam berdasarkan tanggapan tes berbeda. Studi ini berfokus pada lima indikator: memahami komponen statistik, menafsirkan pesan, mengkomunikasikan pesan, mengambil keputusan, dan mengevaluasi informasi statistik secara kritis. Hasilnya menunjukkan tingkat literasi statistik yang bervariasi di kalangan siswa, dengan 72,5% memahami komponen statistik tetapi mengalami penurunan kemampuan dalam menafsirkan (65,2%), berkomunikasi (41,7%), membuat keputusan (38,9%), dan mengevaluasi informasi secara kritis (38,0%). Analisis mendalam terhadap respons siswa menggambarkan kesalahan konseptual dan tantangan dalam menerapkan konsep statistik pada skenario pengambilan keputusan praktis. Studi ini menekankan pentingnya mengembangkan keterampilan analitis dan menerapkan konsep statistik dalam kehidupan sehari-hari untuk meningkatkan kemampuan siswa dalam mengevaluasi informasi secara kritis dan membuat keputusan yang tepat.